Sosialisasi Pemahaman Larangan Undang-Undang Informasi Dan Transaksi Elektronik Serta Etika Penggunaan Media Sosial Pada Remaja - Lefri Mikhael (Faculty of Law Pattimura University, 2022)
Introduction: Technological advances have an impact on the ease of use of social media as a means of socializing between humans. This facility can have a negative impact on society, especially on teenagers who are still in the music video, in the form of crime.Purposes of Devotion: The activity aims to enrich the understanding of the youth members of Karang Taruna Dukuh Sidorejo regarding the prohibition rules in the ITE Law and the ethics required in using social media. Method of Devotion: The activities are delivered in the form of counseling by the delivering material’s method in the form of lectures ending with a question and answer session between the presenters and the participants.Results of the Devotion: The intensity of the use of social media by youth at Karang Taruna Dukuh Sidorejo needs to be accompanied by an understanding of using social media safely and wisely. Through this activity, it is hoped that the participants will become more aware of the prohibitions on the ITE Law that must be avoided in using social media as well as the ethics, principles, and tips for using social media, in order to be able to use social media properly and avoid the negative impacts of using social media.